Finite horizon nonlinear predictive control by the taylor approximation: application to robot tracking trajectory - Hedjar, Ramdane; Toumi, Redouane; Boucher, Patrick; Dumur, Didier (Zielona Góra: Uniwersytet Zielonogórski)
In industrial control systems, practical interest is driven by the fact that today?s processes need to be operated under tighterperformance specifications. Often these demands can only be met when process nonlinearities are explicitly considered inthe controller. Nonlinear predictive control, the extension of well-established linear predictive control to nonlinear systems,appears to be a well-suited approach for this kind of problems. In this paper, an optimal nonlinear predictive controlstructure, which provides asymptotic tracking of smooth reference trajectories, is presented.
Keywords: nonlinear continuous time predictive control; Taylor approximation; tracking trajectory and robot